Annual Plan 2011-2012 Draft Proposals Government of Meghalaya - Planning Commission (Planning Commission, 2011)
The projected 11th Plan outlay for the State during the Eleventh Five Year Plan is of the order of Rs. 1L 9185.00 crores. the State’s priorities for the 11 Plan are as follows:- Power generation, transmission, grid connectivity and rural electrification. Agriculture and allied sectors with strong emphasis on horticulture including post harvesting management and processing. Roads and Bridges for ensuring better connectivity. Sericulture & Weaving for generation of income and employment to the women folk. Tourism infrastructure and tourism services. Trade with Bangladesh and creation of infrastructure for the same.
Planning Department Government of Meghalaya